Urgency of Counseling in the Asean Economic Community (AEC) Era: Opportunities and Challenges - Fini Alfionita Umar; Annas Salahudin (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Counseling services as a field that helps in facing and overcoming the challenges caused by the Asean Economic Community (AEC). The purpose of this study was to determine the urgency of guidance and counseling in the AEC era. The research method uses a literature review. Literature searches for scientific journal articles on Google, Google Scholar, and Research Gate. The results of the research found that the Asean Economic Community is one of the largest markets in Southeast Asia involving 10 countries. Guidance and Counseling is a field that plays a role and overcomes the challenges that arise due to the implementation of the Asean Economic Community. The conclusion of the study reveals that Guidance Counseling is a field that plays a role and overcomes the challenges arising from the implementation of the ASEAN Economic Community (AEC). The contribution of this research as a source of scientific knowledge information both theoretically and practically about the role of guidance and counseling in the AEC era. As well as a research novelty.